Quantifying risk of early relapse in patients with first demyelinating events: Prediction in clinical practice - Spelman, Tim; Meyniel, Claire; Rojas, Juan Ignacio; Lugaresi, Alessandra; Izquierdo, Guillermo; Grand'Maison, Francois; Boz, Cavit; Alroughani, Raed; Havrdova, Eva; Horakova, Dana; Iuliano, Gerardo; Duquette, Pierre; et al. (Multiple sclerosis (Houndmills, Basingstoke, England), 2017)
BACKGROUND: Characteristics at clinically isolated syndrome (CIS) examination assist in identification of patient at highest risk of early second attack and could benefit the most from early disease-modifying drugs (DMDs). OBJECTIVE: To examine determinants of second attack and validate a prognostic nomogram for individualised risk assessment of clinical conversion. METHODS: Patients with CIS were prospectively followed up in the MSBase Incident Study. Predictors of clinical conversion were analysed using Cox proportional hazards regression. Prognostic nomograms were derived to calculate conversion probability and validated using concordance indices. RESULTS: A total of 3296 patients from 50 clinics in 22 countries were followed up for a median (inter-quartile range (IQR)) of 1.92 years (0.90, 3.71). In all, 1953 (59.3%) patients recorded a second attack. Higher Expanded Disability Status Scale (EDSS) at baseline, first symptom location, oligoclonal bands and various brain and spinal magnetic resonance imaging (MRI) metrics were all predictors of conversion. Conversely, older age and DMD exposure post-CIS were associated with reduced rates. Prognostic nomograms demonstrated high concordance between estimated and observed conversion probabilities. CONCLUSION: This multinational study shows that age at CIS onset, DMD exposure, EDSS, multiple brain and spinal MRI criteria and oligoclonal bands are associated with shorter time to relapse. Nomogram assessment may be useful in clinical practice for estimating future clinical conversion.
Keywords: Nomograms; recidiva; proporcionální rizikové modely; Humans; demyelinizační nemoci; MRI; lidé středního věku; Proportional Hazards Models; Multiple Sclerosis; Disease Progression; clinically definite multiple sclerosis; disease-modifying drugs; Female; rizikové faktory; dospělí; CSF; lidé; nomogramy; imunosupresiva; second attack; clinically isolated syndrome; Adult; Immunosuppressive Agents; ženské pohlaví; roztroušená skleróza; Male; Nomogram; Middle Aged; Demyelinating Diseases; prognóza; MS; Recurrence; progrese nemoci; věk při počátku nemoci; mužské pohlaví; Age of Onset; CIS; Prognosis; Risk Factors